2016
DOI: 10.21649/akemu.v22i4.1469
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Foetal Outcome in Cases of Placenta Previa, Accreta and Increta

Abstract: Objective: To evaluate the maternal and foetal outcome in cases of placenta previa, placenta accrete and placenta increta. Methods: Medical records of patients from 1 Feb 2014 to 28 Feb 2015 were checked and patients who underwent caesarean section with a diagnosis of placenta previa types III and IV (and placenta accreta, increta and percreta) were identified. Their medical record files were retrieved and data collected regarding patients age, parity, previous LSCS, D&C, blood loss, bladder injury, hysterecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
5
0
1
Order By: Relevance
“…Similar results with high morbidity and low mortality have been reported in a study from Lahore but number of patients was less. 18 High maternal mortality has been reported from Tanzania and India mainly due to lack of antenatal care. 9 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results with high morbidity and low mortality have been reported in a study from Lahore but number of patients was less. 18 High maternal mortality has been reported from Tanzania and India mainly due to lack of antenatal care. 9 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Similar morbidity is reported from all studies worldwide. [2][3][4][5][11][12][13][14][17][18][19] We had low case fatality of 3% as only two patients died. Antenatal care played an important part in improved outcome of these patients as 86.1% of our patients were booked.…”
Section: Position Of Placenta Is An Important Determinantmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found by Memon E and et al [10] . Another study reported comparative findings but their sample size was small [24] . Su HW in Taiwan had less successful results with conservative management of abnormally invasive placenta to save the uterus and had more morbidity [16] .…”
Section: Discussionmentioning
confidence: 97%
“…Placenta accreta is the abnormal insertion of the placenta to the uterine wall beyond the fibrin layer or Nitabuch layer (1), secondary to total or partial decidual absence (2), with trophoblast villi penetration into the myometrium and even into the serosa or adjacent organs (3,4). Three variants of placenta accreta have been proposed according to the degree of trophoblast invasion: accreta, increta and percreta (5).…”
Section: Introductionmentioning
confidence: 99%